2017
DOI: 10.1002/14651858.cd009984.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological interventions for acute pain after open heart surgery

Abstract: Background Acute postoperative pain is one of the most disturbing complaints in open heart surgery, and is associated with a risk of negative consequences. Several trials investigated the effects of psychological interventions to reduce acute postoperative pain and improve the course of physical and psychological recovery of participants undergoing open heart surgery. Objectives To compare the efficacy of psychological interventions as an adjunct to standard care versus standard care alone or standard care plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 165 publications
1
23
1
1
Order By: Relevance
“…The existing literature on the effectiveness of perioperative psychological interventions is mixed. For instance, a Cochrane review and meta-analysis on perioperative psychological interventions in heart surgery patients revealed no impacts on postsurgical pain [36]. Only two studies measured analgesic use, as measured via PCA use in the hospital, and no effects were found for psychological interventions at this early stage of surgical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature on the effectiveness of perioperative psychological interventions is mixed. For instance, a Cochrane review and meta-analysis on perioperative psychological interventions in heart surgery patients revealed no impacts on postsurgical pain [36]. Only two studies measured analgesic use, as measured via PCA use in the hospital, and no effects were found for psychological interventions at this early stage of surgical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…27,63 Inclusion of simple psychosocial and psychophysical assessment, or "phenotyping" in studies may allow estimation of important differences in pain processing between individuals, 13 informing more accurate prediction of which patients may struggle with pain in the early postoperative period, and allow better targeting of trials of novel analgesic drugs or therapies in "high-risk" samples, increasing study power. 66 This phenotyping of patients is a step towards greater personalization of care, and may allow more effective and targeted preventive perioperative planning.…”
Section: Resultsmentioning
confidence: 99%
“…A Cochrane review by Ziehm et al (2017) indicated that psychological interventions reduce mental distress in patients undergoing cardiac surgery [67]. Additionally, in a Cochrane review by Powell et al (2016) on psychological preparation targeting adults under general anesthesia improved postoperative pain, LOS, negative affect, and behavioral recovery [37].…”
Section: Further Evidence For Effects Of Psychological Interventions mentioning
confidence: 99%